Antarctic Active Subglacial Lake Inventory from ICESat Altimetry - Fricker, Helen; Joughin, Ian; Smith, Ben; Tulaczyk, Slawek (IEDA: US Antarctic Program Data Center, 2012)
This data set contains lake boundaries, volume changes, and gridded elevations for 124 active subglacial lakes beneath the Antarctic ice sheet. Lakes were identified using laser altimetry data obtained from 2003 to 2009 by NASA's Ice, Cloud, and Land Elevation Satellite (ICESat) mission. The data are provided in Keyhole Markup Language (KML), comma-separated values (CSV), and GEOTiff formats.